Possibility of Potentially Inappropriate Medication at Admission and Discharge Among Older People Patients in Emergency Department Using the 2019 Beers Criteria - Hamidah, Khusnul Fitri; Puspitasari, Arina Dery; Dharmayati, Evy; Maryska, Chrysnanda; Kusumawardana, Adi Slamet; Rahman, Firman Suryadi; Rahmadi, Mahardian; Kriswidyatomo, Prihatma; Suprapti, Budi (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Elderly patients are associated with an increasing prevalence of chronic degenerative diseases which need emergency services which can be a factor in the occurrence of potentially inappropriate medication (PIM). The use of PIM increases the risk of patients requiring hospitalization, drug-related problems, and adverse health outcomes with a prevalence of up to 2–3 times. AIM: This study aimed to determine the possible incidence of admission and discharge events on PIM in Elderly patients (>60 years old) visiting the emergency department (ED). MATERIALS AND METHODS: This is a retrospective and observational study at Universitas Airlangga Teaching Hospital in Surabaya for 4 months. This study involved Elderly patients who visited the ED. The 2019 Beers criteria were used to identify the use of PIM. Spearman rho analysis was used to determine the relationship between the possibility of hospital admission and the discharge of patients with PIM. RESULTS: Most patients were female (50.4%) and aged 60−96. The percentage of elderly patients who received PIM and hospital admission was 73.1%, while those who received PIM and hospital discharge were 26.9%. The Spearman rho analysis showed a weak relationship between the possibility of hospital admission or discharge (p-value 0.000, R 0.255) with PIM. CONCLUSION: There is a weak but significant correlation between PIM and patient admission and discharge. Elderly patients are more at risk of being hospitalized due to PIM. The number of ED patients who received PIM had a high prevalence of being hospitalized compared to patients who did not receive PIM.